STRATEGI PENYELESAIAN PEMBIAYAAN MURABAHAH BERMASALAH PADA BMT AGAM MADANI NAGARI KAPAU - Rahma Meli Putri; Rini Elvira (BORJUIS: JURNAL OF ECONOMY, 2025)
Problematic financing is a situation where in its implementation there is a breach of contract due to the customer's inability or difficulties experienced by the debtor in fulfilling obligations or in repayment of installments, and not fulfilling the requirements promised to the creditor. Murabahah products are one of the superior financing products at BMT Agam Madani Nagari Kapau. The most important basic principle of BMT is to collect funds from the community and distribute them to the community. This article aims to examine the factors causing problematic financing of Murabahah bil Wakalah contracts at BMTPAS and strategies for resolving problematic financing carried out by BMT PAS. This research method uses a field research method with a qualitative approach where data sources are collected through interviews and field observations as well as documentation studies related to the resolution of problematic financing. The research results show that the causes of financing problems at BMT PAS come from internal factors of BMT and external factors from errors by financing members. Resolving Problematic Financing by mitigating risks at the outset by always paying attention to the 5K principles, namely Character, Capacity, Capital, Collateral and Condition. The strategy for resolving problematic financing is carried out by repeated billing, through deliberation with a persuasive or family approach, and writing off receivables including write-offs and write-offs, and holding committee meetings, and providing warning letters to customers